THE STEP-BY-STEP METHODOLOGY OF FORMING COMPETENT PERSONNEL - Normatova Muqaddas Baxodirovna; Normatova Muqaddas Baxodirovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article explores the theoretical and practical foundations of forming competent personnel in the context of globalization, digital transformation, and educational modernization. It presents a step-by-step methodology that integrates needs analysis, competence-based education, innovative teaching technologies, and lifelong professional development. The paper also discusses socio-psychological and motivational factors influencing competence formation. The research concludes that a scientifically grounded and continuously improved methodology for forming competent personnel contributes to national competitiveness, sustainable economic growth, and human capital development.